The Origins of Back-End Sentencing in California: A Dispatch from the Archives - Mayeux, Sara (2011)
In recent years, policy analysts have generated a small body of literature about the practice of back-end sentencing, observing that California uses parole revocation in lieu of criminal prosecution for a surprisingly high number of cases, including many that would otherwise be considered serious crimes. Some of these offenders may be getting away with far shorter sentences than if their conduct were prosecuted criminally. Surely others are being railroaded into serving time for charges of which they could never be convicted beyond a reasonable doubt. And many are being cycled in and out of prison on fairly minor violations for which a state prison stay, even a short one, may be overkill